Public knowledge and confidence in the use of public access defibrillation. Issue 12 (29th April 2015) - Brooks, Ben; Chan, Stephanie; Lander, Peter; Adamson, Robbie; Hodgetts, Gillian A; Deakin, Charles D
Abstract : Introduction: Growing numbers of public access defibrillators aim to improve the effectiveness of bystander cardiopulmonary resuscitation prior to ambulance arrival. In the UK, however, public access defibrillators are only deployed successfully in 1.7% of out-of-hospital cardiac arrests. We aimed to understand whether this was due to a lack of devices, lack of awareness of their location or a reflection of lack of public knowledge and confidence to use a defibrillator. Methods: Face-to-face semistructured open quantitative questionnaire delivered in a busy urban shopping centre, to identify public knowledge relating to public access defibrillation. Results: 1004 members of the public aged 9–90 years completed the survey. 61.1% had been first aid trained to a basic life support level. 69.3% claimed to know what an automatic external defibrillator was and 26.1% reported knowing how to use one. Only 5.1% knew where or how to find their nearest public access defibrillator. Only 3.3% of people would attempt to locate a defibrillator in a cardiac arrest situation, and even fewer (2.1%) would actually retrieve and use the device. Conclusions: These findings suggest that a lack of public knowledge, confidence in using a defibrillator and the inability to locate a nearby device may be more important than a lack of defibrillators themselves. Underused public access defibrillation is a missed opportunity to save lives, and improving this link in the chain of survival may require these issues to be addressed ahead of investing more funds in actual defibrillator installation.